Dehydrated alfalfa pellets and soybean meal/grain sorghum in step-up winter supplementation programs for spring-calving beef cows - E.S. Vanzant; R.C. Cochran; L.R. Corah; G.H. Kiracofe (Kansas Agricultural Experiment Station Research Reports, 1991)
The performance response to a stepwise increase in the level of supplement fed to cows across the winter supplementation period was studied by feeding 112 Hereford x Angus cows the following treatments: dehydrated alfalfa pellets (DEHY) or soybean meal/grain sorghum (SS), each either level-fed (constant daily amount from December 1 to calving) or fed in a step-up program (low level from December 1 to 30; moderate level from December 31 to January 29; high level from January 30 to calving; avg = amount fed with level-feeding). Cow weight and condition changes and calf performance were favored by the step-up supplementation program when SS was fed. When DEHY was fed, cow weight and condition changes favored level-feeding. Weight and condition changes generally favored the DEHY group over the SS group. No effects were found for the reproductive characteristics measured. These results indicate that potential benefits of step-up winter supplementation programs depend on the type of supplement being fed. All of the supplementation programs appeared adequate to support desirable levels of reproductive performance.
Keywords: Cattlemen' s Day; 1991; Kansas Agricultural Experiment Station contribution; no. 91-355-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 623; Beef; Beef cows; Protein supplement; Dehydrated alfalfa pellets; Winter range